Long-term impact of dyslipidemia on sac dynamics after endovascular aortic repair for abdominal aortic aneurysms in the GREAT registry: an insight in dyslipidemia using propensity matched controls - Mwipatayi, Bibombe P.; Dodd, James E; Thomas, Shannon D; Chou, Elizabeth L; Milner, Ross; Azizzadeh, Ali; Trimarchi, Santi; Heyligers, Jan MM; Böckler, Dittmar; Schlaich, Markus P (Vascular, 2025)
Objectives - To investigate the differences in aneurysmal sac regression after endovascular aortic repair (EVAR) of abdominal aortic aneurysms (AAAs) in patients with and without dyslipidemia. - Methods - This was a retrospective analysis of 3453 patients from an international prospective registry (Europe, United States of America, Brazil, Australia, and New Zealand) of patients treated with the GORE® EXCLUDER® endograft. All scheduled EVARs for infrarenal AAAs between 2014 and 2016 with complete 6-year follow-up imaging data were included. Logistic regression analysis was performed to assess changes in aneurysm diameter based on dyslipidemia after adjusting for sex, age, body mass index, tobacco use, hypertension, coronary artery disease, aneurysm diameter, aneurysm neck length, and aneurysm neck angle. The secondary outcomes included all-cause mortality, stroke/transient ischemic attack (TIA), paraplegia/paraparesis/spinal cord ischemia, reintervention, endoleaks, and aortic rupture. A control group of patients without dyslipidemia with similar age and comorbidities was selected using propensity scores and matched using a 1:1 scheme. - Results - Of the 3453 patients, 85.3% in the non-dyslipidemia group and 85.5% in the dyslipidemia group were men. The mean age was 73.5 ± 8.8 years for the non-dyslipidemia group and 73.4 ± 8.2 years for the dyslipidemia group (p < .001). The mean body mass index was 26.7 ± 4.9 kg/m2 for the non-dyslipidemia group, whereas it was 28.0 ± 5.2 kg/m2 for the dyslipidemia group (p < .001). Overall, 2269 patients (64.0%) were identified as having dyslipidemia. After propensity score matching (PSM), the dyslipidemia group had higher rates of hypertension (p < .001), TIA (p = .006), carotid disease (p = .002), coronary artery bypass grafting (p = .005), congestive cardiac failure (p = .018), and peripheral artery disease (p < .001). The indications for device placement were similar between the groups. After PSM, the non-dyslipidemia group was more likely to be treated off-label (p = .030) and to have an aneurysm neck length of <15 mm (p = .035). There was no significant difference in the sac size changes within 1 year (p = .7) or 6 years (p = .14) between the groups. After PSM, all-cause mortality was 6.7% in individuals with dyslipidemia and 10.6% in those without (p = .018). However, there were no significant differences in aortic-related mortality between the overall (p = .571) and the matched (p = .662) populations. The rates of reintervention, stroke/transient ischemic attack, and spinal cord ischemia were not significantly different. Among patients with dyslipidemia, larger aneurysm size at 1 year (p = .037) and increased age at 6 years (p < .001) were associated with sac expansion. - Conclusion - In this comprehensive real-world study of patients who underwent EVAR with the GORE® EXCLUDER endoprosthesis found that dyslipidemia did not increase endoleak rates or worsen imaging outcomes over 6 years. Overall, these findings suggest that dyslipidemia does not negatively impact EVAR outcomes and may indicate improved long-term care.